Дослідження факторів впливу на дисперсію пробивної напруги емальдроту з подвійною ізоляцією на основі поліімідних співполімерів - Гурин, Анатолій Григорович; Антонець, С. Ю.; Голик, Оксана Вячеславівна (НТУ "ХПІ", 2012)
Виконано аналіз результатів контролю дисперсії напруги пробою емальпроводу з подвійною ізоляцією на основі поліімідних сополімерів.

The analysis of monitoring data of sigma breakdown voltages in the enameled wire with double isolation on a basis of polyamide copolymers is resulted.
Research of factors influencing to the sigma dielectric breakdown voltage in enameled wire with double isolation on a basis of polyamide copolymers
Keywords: обладнання електротехнічне; надійність; якість; enameled wire; double isolation; breakdown voltage; monitoring data